2016
DOI: 10.1101/gad.271890.115
|View full text |Cite
|
Sign up to set email alerts
|

Mice deficient in poly(C)-binding protein 4 are susceptible to spontaneous tumors through increased expression of ZFP871 that targets p53 for degradation

Abstract: Poly(C)-binding protein 4 (PCBP4), also called MCG10 and a target of p53, plays a role in the cell cycle and is implicated in lung tumor suppression. Here, we found that PCBP4-deficient mice are prone to lung adenocarcinoma, lymphoma, and kidney tumor and that PCBP4-deficient mouse embryo fibroblasts (MEFs) exhibit enhanced cell proliferation but decreased cellular senescence. We also found that p53 expression is markedly reduced in PCBP4-deficient MEFs and mouse tissues, suggesting that PCBP4 in turn regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…ª 2020 The Authors EMBO Molecular Medicine 12: e10895 | 2020 transcriptome profile induced by FST317 overexpression was distinct from that induced by FST344 overexpression (Appendix Fig S5A, Table EV2). Specifically, the differentially expressed gene RAS oncogene family like 6 (RABL6, also known as RBEL1 and C9orf86) (Hagen et al, 2014), CD93 (Iwasaki et al, 2015), and Zinc Finger Protein 709 (ZNF709) (Yan et al, 2016) have been implicated in cancers and leukemia. Upregulation of PRTFDC1 and PODXL2 expression was correlated with poor survival of AML, whereas downregulation of CCNL1 and RP11-762I7.5 was correlated with poor survival of AML (Appendix Fig S5B).…”
Section: Fst Potentiates Mapk/erk Signaling To Promote Leukemia Cell mentioning
confidence: 99%
“…ª 2020 The Authors EMBO Molecular Medicine 12: e10895 | 2020 transcriptome profile induced by FST317 overexpression was distinct from that induced by FST344 overexpression (Appendix Fig S5A, Table EV2). Specifically, the differentially expressed gene RAS oncogene family like 6 (RABL6, also known as RBEL1 and C9orf86) (Hagen et al, 2014), CD93 (Iwasaki et al, 2015), and Zinc Finger Protein 709 (ZNF709) (Yan et al, 2016) have been implicated in cancers and leukemia. Upregulation of PRTFDC1 and PODXL2 expression was correlated with poor survival of AML, whereas downregulation of CCNL1 and RP11-762I7.5 was correlated with poor survival of AML (Appendix Fig S5B).…”
Section: Fst Potentiates Mapk/erk Signaling To Promote Leukemia Cell mentioning
confidence: 99%
“…Interestingly, our laboratory recently demonstrated that PCBP4, a KH domain containing RBP and target of p53 (44), indirectly regulates p53 protein levels by modulating the mRNA stability of ZNF709. Knockout of PCBP4 led to increased ZNF709 protein expression ultimately leading to decreased p53 via a proteasome-dependent degradation pathway (45). These lines of evidence further solidify the overwhelming complexity of p53 regulation and open up the possibility for potential therapeutic intervention by modulating the regulation of p53 by RBP's.…”
Section: Regulation Of P53mentioning
confidence: 67%
“…The p21 3’UTR, known to contain an RBM38-binding site, was used as positive control (Figure 3B , lanes 11-12) [ 19 , 22 ]. The ZFP871 3’UTR [ 28 ] without an RBM38-binding site was used as negative control (Figure 3C ). Furthermore, we found that the probe E-protein complex was super-shifted with anti-RBM38 (Figure 3D ) or inhibited by an excess amount of cold p21 probe (Figure 3E ).…”
Section: Resultsmentioning
confidence: 99%
“…p63γ 3’UTRs were PCR-amplified using forward primers containing T7 promoter sequence and reverse primers as listed in Table 1 . The p21 [ 19 ] and ZFP871 [ 28 ] probes were generated as previously described and used as positive and negative control, respectively. RNA probes were made from in vitro transcription with T7 RNA polymerase in the presence of α- 32 P-UTP.…”
Section: Methodsmentioning
confidence: 99%